Repeated Isoflurane Exposures Impair Long-Term Potentiation and Increase Basal GABAergic Activity in the Basolateral Amygdala - Long Ii, Robert P (Neural plasticity, 2016)
After surgery requiring general anesthesia, patients often experience emotional disturbances, but it is unclear if this is due to anesthetic exposure. In the present study, we examined whether isoflurane anesthesia produces long-term pathophysiological alterations in the basolateral amygdala (BLA), a brain region that plays a central role in emotional behavior. Ten-week-old, male rats were administered either a single, 1 h long isoflurane (1.5%) anesthesia or three, 1 h long isoflurane exposures, separated by 48 h. Long-term potentiation (LTP) and spontaneous GABAergic activity in the BLA were studied 1 day, 1 week, and 1 month later. Single isoflurane anesthesia had no significant effect on the magnitude of LTP. In contrast, after repeated isoflurane exposures, LTP was dramatically impaired at both 1 day and 1 week after the last exposure but was restored by 1 month after the exposures. Spontaneous GABAA receptor-mediated IPSCs were increased at 1 day and 1 week after repeated exposures but had returned to control levels by 1 month after exposure. Thus, repeated exposures to isoflurane cause a long-lasting-but not permanent-impairment of synaptic plasticity in the BLA, which could be due to increased basal GABAergic activity. These pathophysiological alterations may produce emotional disturbances and impaired fear-related learning